KARAKTERISTIK PRODUK DARI ESTERIFIKASI DENGAN BANTUAN GELOMBANG ULTRASONIK TERHADAP MINYAK BIJI KAPUK TEROZONASI - Haryono; Engela Evy Ernawati; Atiek Rostika Noviyanti (Jurnal Penelitian Hasil Hutan, 2022)
The kapok seed oil is non-edible oil so it is very profitable as a raw material for making biodiesel. However, the kapok seedoil is dominated by long chain and unsaturated fatty acids. These types of fatty acids tend to reduce the quality of biodiesel, namelythe low cetane number and trigger polymerization reactions during combustion. Ozonation could be applied to shorten the carbonchain and the number of double bonds in fatty acids from kapok seed oil. This research aims to study the effect of time of ozonationat preparation stage of kapok seed oil on biodiesel characteristics of esterification stage with the assistance of ultrasonic waves. Theozonation time was varied for 60, 90, and 120 minutes. The results showed that the longer the time of ozonation the kapok seedoil produced with the increased acid number. The greater acid number of the kapok seed oil was verified by the fatty acid compositionof Gas Chromatography-Mass Spectroscopy analysis, showed that the fatty acid structure of the kapok seed oil became simpler.The esterification for 120 minutes to ozonated kapok seed oil which has been ozonized produces oil phase with an acid number of10.6 mg KOH/g, a saponification number of 112 mg KOH/g, and a density of 903 kg/m3.